2020
DOI: 10.1044/2020_jslhr-20-00198
|View full text |Cite
|
Sign up to set email alerts
|

Language Development From Early Childhood to Adolescence in Youths With Fragile X Syndrome

Abstract: Purpose The aim of this study was to investigate language growth in individuals with fragile X syndrome (FXS) from early childhood to adolescence and the influence of maternal responsivity on language growth. Method We conducted a longitudinal analysis of language development in 55 youths (44 males, 11 females) with FXS. Data collection spanned the ages of 11–216 months. We measured expressive and receptive vocabulary with standardized tests. The number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Beyond this, it is not clear when children with FXS begin to combine words and use phrases. Nonetheless, expressive language skills do increase over time Brady et al, 2020 ) with many individuals with FXS using spoken language. In a study of boys with FXS between 21 and 77 months ( Roberts et al, 2007 ), performance on verbal and vocal communication domains (e.g., use of vocalizations, different words, and word combinations) were higher than performance on gestural communication, reciprocity (responding to communicative acts, repair strategies), and symbolic communication (e.g., language comprehension, constructive play) during the direct administration of the CSBS-Behavior Sample ( Wetherby & Prizant, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond this, it is not clear when children with FXS begin to combine words and use phrases. Nonetheless, expressive language skills do increase over time Brady et al, 2020 ) with many individuals with FXS using spoken language. In a study of boys with FXS between 21 and 77 months ( Roberts et al, 2007 ), performance on verbal and vocal communication domains (e.g., use of vocalizations, different words, and word combinations) were higher than performance on gestural communication, reciprocity (responding to communicative acts, repair strategies), and symbolic communication (e.g., language comprehension, constructive play) during the direct administration of the CSBS-Behavior Sample ( Wetherby & Prizant, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Broadly, research on comprehension indicates that while overall receptive language skills are delayed for children with FXS ( Finestack et al, 2013 ; Roberts, et al, 2007 ), they do show increases in receptive language abilities over time ( Brady et al, 2020 ). Like expressive language abilities, studies of children and adolescents have not found significant differences between those with FXS + autism and those with FXS only ( McDuffie et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some individuals with FXS meet diagnostics criteria for ASD, and those with ASD have been reported to have poorer language outcomes (Haebig et al, 2020), and tend to have more impaired cognition (Haebig et al, 2020). Sometimes it can be difficult to determine if language outcomes are more affected by IQ or autism status (Brady et al, 2020). One aim of the present investigations is to assess the influence of language on social perception and executive functions in girls with FXS.…”
Section: Methodsmentioning
confidence: 99%
“…In an ongoing longitudinal study of 55 children with FXS (11 girls) and their mothers, the findings indicated that, while language proficiency continues to be very delayed for most participants, positive slopes were detected for vocabulary measured by standardized test. Rates of number of different words grew steadily for most participants until age of 10 years and then decreased somewhat (Brady et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, FXS illustrates the complexity of symptoms and the challenges in communication between caregivers and healthcare professionals seen in most NDDs. Indeed, individuals with FXS present clinically with a wide spectrum of symptoms and comorbid conditions, including core cognitive and adaptive function challenges (25), speech delay (26,27), autism spectrum traits (28)(29)(30)(31), sleep issues (32)(33)(34), challenging behavior (35), anxiety (36), and mental health issues (37). FXS is also an excellent model for understanding changing needs over a lifespan as, like most NDDs, it is a lifelong condition where the health, educational, and social needs of individuals evolve over time, making care even more complex and challenging for parents and health professionals (38).…”
Section: Fragile X Syndrome As a Model For Complex Care In Nddmentioning
confidence: 99%